FEATURES OF THE CHARACTERISTICS OF VICTIMS OF CRIMINAL OFFENCES COMMITTED BY PROFESSIONAL PARTICIPANTS OF THE JUDICIAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2025)
The article highlights the importance of the victim in criminal proceedings concerning crimes against justice committed by professional participants in the judicial process, particularly as an object of encroachment and a source of evidence. It justifies the necessity of gathering comprehensive information about the victim as a crucial condition for ensuring a thorough, objective, and unexpected investigation. Based on an analysis of data from the Unified State Register of Court Decisions, typical socio-demographic features of victims are identified, with adult Ukrainian citizens who engage in public activities or have prior criminal records being most common. The article proposes categorizing victims into two main groups: unprotected persons and individuals of investigative or operational interest. A refined interpretation of each category is provided, considering their characteristics and potential influence on the progress of criminal proceedings. It emphasizes that such an approach to studying the victim's personal circumstances enhances understanding of the causes and conditions behind crimes against justice, leading to more effective evidence collection.
Keywords: justice; professional participant in legal proceedings; forensic characteristics; mechanism of crime; victim